2011
DOI: 10.2459/jcm.0b013e328343d708
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial blood flow and infarct size after CD133+ cell injection in large myocardial infarction with good recanalization and poor reperfusion: results from a randomized controlled trial

Abstract: These findings support the hypothesis that intracoronary administration of bone marrow-derived, but not peripheral blood-derived CD133 cells 10-14 days after STEMI may improve long-term perfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…After the exclusion of 141 review articles, full-text analysis was performed on 173 reports, of which 64 were excluded because of unrelated outcomes; 27 were excluded due to the use of G-CSF; 19 were cohort studies; and 15 articles represented additional publications from previously reported trials, leaving forty-eight RCTs 5,6,1114,1620,2224,2863 (enrolling a total of 2602 patients) for inclusion in the final analysis (Figure 1). …”
Section: Resultsmentioning
confidence: 99%
“…After the exclusion of 141 review articles, full-text analysis was performed on 173 reports, of which 64 were excluded because of unrelated outcomes; 27 were excluded due to the use of G-CSF; 19 were cohort studies; and 15 articles represented additional publications from previously reported trials, leaving forty-eight RCTs 5,6,1114,1620,2224,2863 (enrolling a total of 2602 patients) for inclusion in the final analysis (Figure 1). …”
Section: Resultsmentioning
confidence: 99%
“…After 10 years of GMP activity, our center can claim to have multidisciplinary experience in the field of regenerative medicine [5][6][7][8][9][10][11][12].…”
Section: Our History and Authorizationmentioning
confidence: 99%
“…These encouraging results were confirmed in the following phase II clinical study demonstrating improved LVEF and myocardial perfusion 6 month after SC transplantation compared to the standard therapy group [88]. To date, several phase I and II clinical trials reported the safety, feasibility and beneficial effects of intramyocardially [89,90] and intracoronary [91][92][93][94][95] injected BM-derived CD133 + cells for the treatment of cardiac diseases. However, long term follow-up studies failed to show an improved cardiac function in SC treated patients after several years [96,97].…”
Section: Bm-derived Hscs and Epcsmentioning
confidence: 48%